The iPhone book : how to do the most important, useful & fun stuff with your iPhone - Kelby, Scott (Peachpit ; Pearson Education [distributor], 2013)
Presents an introduction to the features and functions of the iPhone, covering everything from the gadget's keyboard, built-in GPS, new App store, and MobileMe to its communication, e-mail, and Internet functions.